Characteristics and Genetic Mechanism of Chang Eight Low Permeability and Tight Reservoir of Triassic Yanchang Formation in Central-East Ordos Basin - Wang, Xingying; Liu, Na; Nan, Junxiang; Wang, Xiaolin; Ren, Dazhong (Frontiers in Physics, 2022)
In this paper, the characteristics of Chang 8 reservoir of Triassic Yanchang Formation in Northern Shaanxi are studied by using polarizing microscope, field emission scanning electron microscope, image particle size, X-ray diffraction analysis of clay, and constant pressure mercury intrusion. The study shows that the target layer is in a relatively stable and uniform sinking burial period after deposition, and the lithology composition in the area is relatively complex, mainly composed of debris-feldspar sandstone and feldspar sandstone, with the characteristics of fine grain and high content of interstitial material. The porosity of the reservoir is generally between 4% and 12%, with an average of 8.05%. The permeability is generally between 0.03×10-3μm2 and 0.5×10-3μm2, with an average of 0.16×10-3μm2. Strong compaction and well-developed cementation of calcareous, siliceous and authigenic illite are important reasons for the formation of extra-low porosity and extra-low permeability reservoirs. But at the same time, due to the protective effect of chlorite film, some residual intergranular pores are preserved, which makes the some reservoirs with relatively good physical property, forming a local relatively high porosity and high permeability section of the "highway".